Human rights court in India: Key legal concerns - Choudhary, Karan (Journal of the Indian Law Institute)
This paper shall identify and flag up key legal concerns regarding Human Rights Courts in India as provided for by the Protection of Human Rights Act, 1993 (PHRA). To aid the gestalt comprehension, researcher will first study and analyse the concomitant circumstances which prevailed during the birth of PHRA in India. The legislative design including the institutional framework in terms of establishment of the fourth branch institutions, for the protection and promotion of human rights in India, will be scrutinised. In this context, Human Rights Courts will be analysed. Recent Delhi Gazette Notification F.No. 6/13/2011-Judl./Suptlaw/1132-1137 on November 24, 2020 has designated the court of Additional Sessions Judge in each District as Human Rights Court. It is opportune time to look at the legal concerns regarding such courts and need for immediate interventions, if any. The guiding aim of this research paper is to strengthen the institutional framework to effectively protect and promote human rights in India.- Reproduced